2016
DOI: 10.4148/1944-9771.1110
|View full text |Cite
|
Sign up to set email alerts
|

Money and Emerging Adults: A Glimpse into the Lives of College Couples’ Financial Management Practices

Abstract: Being in a romantic relationship is a transition that many

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 37 publications
2
12
0
Order By: Relevance
“…In this study, we did not focus on the financial impact of children on the relationship, but rather acknowledged that a family's financial needs change with the addition of children who introduce new financial implications to the family unit. Through examination of the direct experiences of six couples, this study reinforces the literature that has quantified the approaches couples can take to ISSN: 1945-7774 CC by-NC 4.0 2018 Financial Therapy Association managing their finances and how this may link to marital quality (Addo & Sassler, 2010;Archuleta, 2008Archuleta, , 2013Pahl, 1995;Rea et al, 2016).…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…In this study, we did not focus on the financial impact of children on the relationship, but rather acknowledged that a family's financial needs change with the addition of children who introduce new financial implications to the family unit. Through examination of the direct experiences of six couples, this study reinforces the literature that has quantified the approaches couples can take to ISSN: 1945-7774 CC by-NC 4.0 2018 Financial Therapy Association managing their finances and how this may link to marital quality (Addo & Sassler, 2010;Archuleta, 2008Archuleta, , 2013Pahl, 1995;Rea et al, 2016).…”
Section: Resultssupporting
confidence: 57%
“…However, the effect of childbirth did not significantly affect money management systems in terms of independent money management or joint pooling (Lott, 2017). Rea, Zuiker, and Mendenhall (2016) used mixed-methods to understand money management practices of students in relationships and found communication in participant's relationships to be an important factor during life transitions and in their own personal financial knowledge. Qualitative research on financial management and marital quality has yet to specifically target married couples with children living in the home.…”
Section: Marital Qualitymentioning
confidence: 99%
“…The intersection of new freedoms and responsibility, adjusting to a new environment, and meeting new people, create new challenges that contribute to the process of relationship formation, maintenance, and dissolution (Madey & Jilek, 2012). It is likely that romantic partners find out about one another's money habits and behaviors during the process of relationship formation, and challenges can occur when partners have opposing financial beliefs (Rea, Zuiker, & Mendenhall, 2016).…”
Section: College Students' Financial Knowledge and Financial Avoidancementioning
confidence: 99%
“…A wealth of research has linked relationship functioning with financial well-being (for better or worse). Handling and navigating finances and money is an important indicator and diagnostic tool of relationship success (Shapiro, 2007), and even college students believe they should communicate about both individual and combined finances with their partner (Rea, Zuiker, & Mendenhall, 2016). Research has found that having shared financial goals and values, and communicating about their individual and combined finances, are important for relationship health, and this has been found in both married samples (Archuleta, 2013) and unmarried college students who are dating (Rea, Zuiker, & Mendenhall, 2016).…”
Section: Finances and Conflictmentioning
confidence: 99%
“…Therefore, the demand for money management assists undergraduates to be wiser and prudent when spending to avoid wasting money. If planning and management are systematically and efficiently implemented, the financial position will be sufficient and may even have a surplus and can be used as a savings (Rea, Zuiker, & Mendenhall, 2016).…”
Section: Introductionmentioning
confidence: 99%